Electrophysiological evidence for the time course of syllabic and sub-syllabic encoding in Cantonese spoken word production. Issue 6 (3rd July 2019) - Wong, Andus Wing-Kuen; Chiu, Ho-Ching; Wang, Jie; Wong, Siu-San; Chen, Hsuan-Chih
ABSTRACT: This study was conducted to investigate the time course of syllabic and sub-syllabic encoding in Cantonese Chinese spoken word production using the picture-word interference task with concurrent recording of event-related brain potential (ERP) signals. Cantonese-speaking participants were asked to name aloud individually presented pictures and ignore an accompanying auditory word distractor. Participants' naming responses were faster, relative to an unrelated control, when the target (e.g. /gu2/, meaning "drum") was presented together with a distractor sharing the same atonal syllable (e.g. /gu 3/), or syllable body (e.g. /gu ng1/). More importantly, the ERP effects associated with syllable-related priming appeared earlier than those associated with body-related priming. The earlier effects of syllable-related priming relative to body-related priming indicate that syllable retrieval precedes sub-syllabic specification in Cantonese phonological encoding, consistent with the proximate unit hypothesis that the nature of the proximate phonological unit (i.e. the first selectable phonological unit following lexical access) is language dependent.